Pengaruh Alokasi Dana Desa Terhadap Kesejahteraan Masyarakat Desa Nagari Batipuah Ateh, Kecamatan Batipuh - Rahim, Febria; Febriyanti, Siska; Candra, Revi; Rahmi, Dhiah Ul; Yenti, Fitri (Universitas Negeri Padang, 2025)
This study aims to examine the impact of village fund allocation on various aspects of community welfare in Nagari Batipuh Ateh, Batipuh District. The research employed a field study with a quantitative approach. Population consisted of 1,423 families in Nagari Batipuh Ateh, Batipuh District. A sample of 93 respondents was selected using the Slovin formula and stratified random sampling technique. Data were collected through questionnaires and documentation. The data were analyzed using statistical tests with SPSS version 26. The results indicate that village fund allocation has a significant impact on various aspects of community welfare, including income, housing and public facilities, health, education, and transportation in Nagari Batipuh Ateh. Therefore, it can be concluded that the four hypotheses are accepted, confirming that village fund allocation positively influences the overall welfare of the community.